Drug-Eluting Nasal Implants: Formulation, Characterization, Clinical Applications and Challenges - Ankit Parikh; Utkarshini Anand; Malachy C. Ugwu; Tiam Feridooni; Emad Massoud; Remigius U. Agu (MDPI AG, 2014)
Chronic inflammation and infection of the nasal sinuses, also referred to as Chronic Rhinosinusitis (CRS), severely affects patients' quality of life. Adhesions, ostial stenosis, infection and inflammation relapses complicate chronic sinusitis treatment strategies. Drug-eluting stents, packings or implants have been suggested as reasonable alternatives for addressing these concerns. This article reviewed potential drug candidates for nasal implants, formulation methods/optimization and characterization methods. Clinical applications and important considerations were also addressed. Clinically-approved implants (Propel™ implant, the Relieva stratus™ MicroFlow spacer, and the Sinu-Foam™ spacer) for CRS treatment was an important focus. The advantages and limitations, as well as future considerations, challenges and the need for additional research in the field of nasal drug implant development, were discussed.